Client-centered exercise prescription - Griffin, John C. (Human Kinetics, 2015)
Expands the role of the fitness professional from simple exercise prescription to include activity counseling, design modification, exercise demonstration, functionally integrated exercise, injury prevention and follow-up monitoring. This book features seven client-centered models for each major fitness component.